Nutritive value of sugarcane silages with different bacterial additives and fermentation periods - Silva,Ivone Rodrigues da (2020)
ABSTRACT The objective of this study was to evaluate the nutritive value of sugarcane silage with or without inoculation with P. acidipropionici or L. buchneri, over three fermentation periods. The experimental design was completely randomized in a 3 x 3 inoculant by fermentation period factorial arrangement (without inoculant, inoculant 1, inoculant 2; x three fermentation periods, 10, 60, 90 days). Values of pH, dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose (HEM) and lignin were determined and in situ DM degradability profiles were modelled for parameters a, b and c, potential degradation (A) and effective degradability (ED). The 90 day fermentation yielded a lower pH for both inoculants. There was an interaction between inoculant and fermentation period (P < 0.05) for DM content, with a reduction in silage DM without the additive at 90 days. The CP, HEM, ADF and lignin contents of sugarcane were not influenced by the treatments. The addition of P. acidipropionici provided the lowest NDF content at 10 days and presented a higher fraction a, potential degradation and ED. At 60 days, there was no variation in soluble fraction, the control silage showed a higher fraction b, higher potential degradation and ED. At 90 days of fermentation, L. buchneri silages presented a higher fraction a, degradation rate and DE and a higher b value was obtained in the silage without inoculant. Inoculants are effective in maintaining the silage DM content and nutritional value during prolonged fermentation periods.